Razvoj in dosežki zgodovinske antropologije likovnega - Mikuž, Jure (Monitor ISH, 2009)
The last decades of the 20th century witnessed new epistemological approaches in the humanities, based on structuralism, post-structuralism, deconstruction,post-Freudian psychoanalysis, semiotics, New Marxism, etc. In the field of historical studies, new scientific horizons opened especially with new history and historical anthropology, while the last discipline to modernise its approaches was traditional art history. Based on visual and cultural studies, social art history, hermeneutics, aesthetics of reception, French semiotics of the visual, neuro-art-history and others, a new interdisciplinary method emerged: the historical anthropology of images
Keywords: likovna umetnost; visual arts; zgodovinska antropologija; umetnostna zgodovina; art history